3x² - 24x - 60 = 0; whence,
x² - 8x - 20 = (x - 10)(x + 2) = 0; and
x = 10 or -2.
Checking, we find that
3(10)² - 24(10) - 60 = 300 - 240 - 60 = 0, and
3(-2)² - 24(-2) - 60 = 12 + 48 - 60 = 0,
thus re-assuring us that we have solved correctly.
15x minus 8=minus 180 3x+8=24
ㅗㅓㅕㅗType your answer here...
3x(x - 5)(x + 5)
It is: (2x+3)(3x-8) when factored
x3 - 3x2 - 28x = x (x2 - 3x - 28) = x (x - 7) (x + 4)The numerical value of all this, of course, depends on the value of 'x',and it can change in a flash whenever the value of 'x' changes.
3x2 -14x -24 can be factored as (3x + 4)(x - 6).
15x minus 8=minus 180 3x+8=24
7x+6 = -3x-24 7x+3x = -24-6 10x = -30 x = -3
3(x - 8)
ㅗㅓㅕㅗType your answer here...
3x(x - 5)(x + 5)
It is: (2x+3)(3x-8) when factored
x3 - 3x2 - 28x = x (x2 - 3x - 28) = x (x - 7) (x + 4)The numerical value of all this, of course, depends on the value of 'x',and it can change in a flash whenever the value of 'x' changes.
(x2 + 3x + 5)(x2 - 3x + 4)
24
If: 8-1/3x = 16 Then: x = -1/24
(3x^2 - 4y^2)(3x^2 + 4y^2)